Tirésias: mito, paixão e cinema - Moura, Gracielly Dias de (2019)
This research is a comparative study between a variant of the Greek myth of Tiresias present in the Biblioteca Mitológica of Apolodoro (2016), and the cinematographic work titled Tiresia, by Bertrand Bonello (France, 2003), which refers to the myth. Tiresias, both in the myth and in the film, experienced being a man, was transformed into a woman, and back to the masculine form, acquiring the gift of clairvoyance. In order to identify the elements of approximation and detachment between the two works, from the postulates of Greimas and Courtés (1979), and from the semioticists Diana de Barros (2002), Fiorin (1995) and Bertrand (2003), we undertake an analysis of the generative path of meaning of the myth and the film, proceeding with the identification of the elements in common in the two works, on different levels of meaning production: the discursive, the narrative and the fundamental one. It is important to investigate what this new media, the film, retains from the myth, and what it adds to it. Therefore, the choice of the semiotic discourse analysis and the generative path of meaning proposed by Greimas is due to the fact that discourse semiotics is a field dedicated to investigating the narrative text from its structure, which presupposes different levels of the meaning production process. After the analysis of the generative path, the analysis of the pathological order is undertaken, according to the work Semiótica das paixões, by Greimas and Fontanille (1998). From the canonical model proposed by the authors, the motor feeling that drives the actants to transition from one state to another is identified, not from the perspective of action and things alone, but from the emotion, which updates the state of the subjects. The main objective of this study is, based on the analyses undertaken, to demonstrate that, even though being equidistant in terms of spatial, temporal and social context of their productions, the two works essentially deal with themes that were dear to man in ancient Greece and are still in the contemporaneity: the dispute of power between the male and female genres driven by the passions of rivalry and jealousy and, at the deepest level of the generative path of meaning, the relationship between nature and culture.